A Novel Multi-compartment Rotating Bioreactor for Improving ADSC-Spheroid Formation and its Application in Neurogenic Erectile Dysfunction - Wang, Peng; Liu, Yang; Duan, Xiao-Feng; Pan, Xiao-Ying; Kong, Xiang-Rui; Yang, Yong (Current Stem Cell Research & Therapy, 2024)
Objective: The aim of this study was to construct a multicompartment synchronous rotating bioreactor (MCSRB) for batch-production of homogenized adipose-derived stem cell (ADSC) microspheres and treat neurogenic erectile dysfunction (ED). Methods: Firstly, an MCSRB was constructed using a centrifugal device and hinged trays. Secondly, influence factors (density, rotational speed) on the formation of ADSC-spheroids were explored. Finally, a neurogenic ED model was established to verify the effectiveness and safety of ADSC-spheroids for ED treatment. Results: An MCSRB promoted ADSCs to gather microspheres, most of which were 90-130 μm in diameter. Supernatant from three-dimensional culture led to a significant increase in cytokine expression in ADSCs and migration rate in human umbilical vein endothelial cells (HUVECs) compared to control groups. The erectile function and pathological changes of the penis were improved in the ADSC-spheroids treatment group compared to the traditional ADSCs treatment group (p < 0.01). Conclusion: Efficient, batch, controlled and homogenized production of ADSC stem cell microspheres, and effective improvement of erectile dysfunction in neurogenic rats can be achieved using the MCSRB device.
Keywords: cavernous nerve damage